The velocity and fatigue index of various leg kicks in rescue towing - Abraldes, J. A.; Stallman, R. K.; Soares, S.; Queiroga, A. C. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
A drowning episode can occur under many different conditions and unfold in many variable ways (1). The condition (active, passive, unconscious, etc.) and size of the victim, the distance from safety (shore, pool deck, pier, etc), the water conditions (waves, temperature, currents, visibility, wind, etc), the experience, knowledge, skill and fitness of the rescuer, availability of rescue equipment, and other variables, make a swimming rescue a very dangerous enterprise indeed. In fact, a growing number of agencies have removed direct contact swimming rescues from their programs of teaching lifesaving to the general public (possible future bystanders) and relegated them to the training of professional lifeguards (2). Possible future bystanders are thus trained to use only swimming rescue towing techniques involving equipment-either specifically designed rescue equipment or more likely, randomly available objects at hand. The motive of course, is to increase the distance between the rescuer and victim, avoiding direct physical contact. The optimal situation in rescue towing is for the rescuer to be versatile enough to be able to select the most appropriate technique relative to the variables named above. This allows the rescuer to make choices but it also demands a broad spectrum of rescue skills. The inexperienced and less versatile rescuer may have no choice except to attempt the rescue or not to attempt the rescue. The need to use perhaps the only technique which this rescuer has mastered, though inappropriate, may jeopardise the rescue and reduce the chances of success. The needs in real rescue, as described here, are many and varied, and usuallyunpredictable. Appropriate training of the general public includes a variety of techniques and the concomitant knowledge to use them, allowing the rescuer some choice, according to the conditions. Lifesaving competition also involves a variety of techniques. Well over a century old, this form of competition has a history of attempting to simulate real rescue situations. As competition has developed, and among other things, has also created an indoor variation, the competition has become more formal. Complex rules have been established (attempting both fair competition and simulated real rescue). The rules of each event are sufficiently rigid to not allow much choice to the rescuer. The distance is fixed, whether or not fins are to be used, whether or not the simulated victim (mannequin) is submerged, whether a rescue device is to be used, and more, are both specified and known in advance (3). We see immediately that the needs of real rescue and competition rescue are not quite the same (4). They have, however, so much in common that research can help us better understand both. Research will also help us identify both similarities and differences between real rescue and simulated rescue in competition. Given that only a few studies have been conducted on rescue towing there is urgent need for further research (2). Several studies have compared towing with the flutter and dolphin kicks, with and without fins (5,6, 7,8). Some have compared different types of fins (9). Still others have examined towing, including both arm and leg strokes (10,11,12,13,14). While performance with fins has been shown to be superior, the most common situation in real rescue is that fins are not available, and also in competition, some events are specified to be performed without fins. To the best of our knowledge, no study has yet compared the scissors kick to other kicks using the legs only without fins, and while performed in the side lying position.